Cohort profile: Thrombolysis in Ischemic Stroke Patients (TRISP): a multicentre research collaboration. Issue 9 (17th September 2018) - Scheitz, Jan F; Gensicke, Henrik; Zinkstok, Sanne M; Curtze, Sami; Arnold, Marcel; Hametner, Christian; Pezzini, Alessandro; Turc, Guillaume; Zini, Andrea; Padjen, Visnja; Wegener, Susanne; Nordanstig, Annika; et al.
Abstract : Purpose: The ThRombolysis in Ischemic Stroke Patients (TRISP) collaboration aims to address clinically relevant questions about safety and outcomes of intravenous thrombolysis (IVT) and endovascular thrombectomy. The findings can provide observational information on treatment of patients derived from everyday clinical practice. Participants: TRISP is an open, investigator-driven collaborative research initiative of European stroke centres with expertise in treatment with revascularisation therapies and maintenance of hospital-based registries. All participating centres made a commitment to prospectively collect data on consecutive patients with stroke treated with IVT using standardised definitions of variables and outcomes, to assure accuracy and completeness of the data and to adapt their local databases to answer novel research questions. Findings to date: Currently, TRISP comprises 18 centres and registers >10 000 IVT-treated patients. Prior TRISP projects provided evidence on the safety and functional outcome in relevant subgroups of patients who were excluded, under-represented or not specifically addressed in randomised controlled trials (ie, pre-existing disability, cervical artery dissections, stroke mimics, prior statin use), demonstrated deficits in organisation of acute stroke care (ie, IVT during non-working hours, effects of onset-to-door time on onset-to-needle time), evaluated the association between laboratory findings on outcome after IVT and served to develop risk estimation tools for prediction of haemorrhagic complications and functional outcome after IVT. Future plans: Further TRISP projects to increase knowledge of the effect and safety of revascularisation therapies in acute stroke are ongoing. TRISP welcomes participation and project proposals of further centres fulfilling the outlined requirements. In the future, TRISP will be extended to include patients undergoing endovascular thrombectomy.